(untitled) (Carte Romanze, 2020)
The paper describes two late fifteenth-century manuscripts of the Biblioteca Civica Centrale of Turin which preserve Petrarch’s works: the first contains exclusively the Secretum, a rare fact in the tradition of this work; the second preserves its epitaph and two metrical epistles (II 5, excerptum and III 24) within a silloge of Latin epigrams of mostly humanistic origin.